Characteristic of Lokon Volcano Deformation of 2009 - 2011 Based on GPS Data - Kriswati, Estu; Meilano, I.; Suhartaman, Suhartaman; Suparman, Y.; Abidin, H. Z.; Sinaga, Tumpal (Indonesian Journal on Geoscience, 2012)
DOI:Â 10.17014/ijog.v7i4.147Precursor of Lokon Volcano eruptions in 2011 is believed to begin since December 2007 which was marked by increasing number of volcanic earthquakes and gas emission. To support this information, deformation method is used primarily to determine deformation characteristics of Lokon volcanic activity in the period of 2009-2011. The period of analysis is adapted to the presence of GPS data. Displacement rate of Lokon GPS observation points in the period of 2009 - 2011 ranged from 1.1 to 7 cm a year. Strain patterns that occur in the areas are compression surrounding Tompaluan crater and extension in the eastern slope. Location of the pressure source for August 2009 - March 2011 measurement was at a depth of 1800 m beneath Tompaluan crater. Deformation in the Lokon Volcano is characteristized by the compression zone in the summit and crater area caused by magma activity raised into the surface from a shallow magma source which is accompanied by a high release of volcanic gases. Accumulated pressure release and deformation rate as measured in the Lokon Volcano remain low.